QASHQADARYO VILOYATIDA TARQALGAN HAQIQIY QALQONLI QANDALALAR (HETEROPTERA: PENTATOMIDAE) FAUNASI - Bo’riyeva X.P., Bo’riyeva X.P.; Qurbonova A; Norqobilova Z.B. (Actual problems and prospects of the study of the fauna, 2024)
This article presents, for the first time, information on the species of true shield bugs distributed in the Kashkadarya region and their ecological groupings. The study also highlights research findings on the oligophagous species Neottiglossa leporina, the monophagous species Chlorochroa pinicola and the polyphagous species Halyomorpha halys.